Charles et ses images - Anne-Marie Baron (Flaubert: Revue Critique et Génétique)
From the 1930s to the present, Charles Bovary is probably the most altered character in the adaptations of Flaubert’s novel. The first directors made a victim of him, but gradually, the cinema began to emphasize his deleterious dimension and attributed to him a large part of the responsibility for Emma’s grief. From Pierre Renoir, touching and authentic, to Gregg Edelman, who fantasizes on a pornographic website in Todd Field’s Little Children, the more or less pathetic or ridiculous portrayals given by Van Heflin, Aribert Wäscher, Alberto Bello, Jean-François Balmer, Farooq Shaikh or Luis-Miguel Cintra, show that more than any other character in the novel, Charles has been submitted to a serious metamorphosis by being interpreted on screen according to each country’s civilization and the successive decades of filming.